Teachers’ perspectives and practice in using learning approaches to foster learner autonomy in Vietnam - Tai Huu Nguyen; Thu Le Anh Tran (Ho Chi Minh City Open University Journal of Science - Social Sciences)
The research paper’s primary objective was to understand teachers’ reflections on the implementation of different learning approaches, including resource-based, curriculum-based, classroom-based, technological-based, teacher-based, and learner-based approaches, to foster Learner Autonomy (LA) of Vietnamese undergraduates. Applying learning approaches to encourage LA has been widely discussed; however, there is a lack of evidence of teachers’ perspective and practice, in relation to their professional experience, of those approaches to cultivating LA. A survey was conducted at the Creative Language Center of Ton Duc Thang University (TDT CLC), Vietnam, to collect responses from lecturers who have different experience in teaching English at the tertiary level. The findings indicate that teachers, regardless of experience, focused more on classroom-based approaches, such as providing cooperative learning and peer discussion to foster LA. However, teachers with more experience tend to focus on learner-based approaches to provide more individual training and assistance to help students become more autonomous learners. Understanding the concept of learning approaches and their implementation is believed to benefit teachers, especially those with less experience, in fostering LA in their own teaching context.